EFFICIENCY INDICATORS SITUATION EUROPEAN CHAMPIONSHIP IN HANDBALL WOMEN'S 2010th - Branko Gardašević; Ivan Terzić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
We analyzed the 47 matches played at the 9th European Championship in Handball, Women, held in Denmark and Norway in December 2010. Observed were 16 teams participating. Recorded in the technical and tactical elements, the phases of attack and defense, more than 250 players. We analyzed the following technical and tactical elements: the number of shots on goal, the success rates, assists, defensive blocks, steals and penalties. Individual performance was correlated with the final team standings. The results confirmed that the team to achieve successful results especially significant individual efficiency in defense phase. This confirms the fact that among the 10 players that have shown the highest degree of efficiency defense is 7 from the three best teams. In this way, once again exactly confirmed that a solid game in defense phase prerequisite for high placement in major competitions. The teams they finished poorly, such as the National Team of Serbia, in this area have demonstrated a number of shortcomings, which among other shows inadequate method of training. The discussion and conclusions are given suggestions for improving existing training practice